2014
DOI: 10.1007/s40121-014-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant 3-Hydroxy-3-Methyl-Glutaryl-CoA Reductase Inhibitor Therapy on Creatine Phosphokinase Levels and Mortality Among Patients Receiving Daptomycin: Retrospective Cohort Study

Abstract: IntroductionThe prescribing information for daptomycin recommends discontinuing statin therapy during receipt of daptomycin. The literature supporting this recommendation is sparse. The objectives of this study were to examine the impact of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase inhibitors (statins) on creatine phosphokinase (CPK) elevations and mortality among patients receiving daptomycin therapy.MethodsA retrospective cohort study was performed among daptomycin recipients in the Upstate New Yor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 14 publications
0
38
1
Order By: Relevance
“…In this study, statins were concomitantly used in six cases; however, none of them induced abnormal CPK elevation, which suggests the safety of the concomitant use of statins. Other previous reports also suggested the safety or insignificance of the concomitant use of statins . On the contrary, a recent clinical study reported that the coadministration of statins was a significant independent risk factor for myopathy and rhabdomyolysis .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, statins were concomitantly used in six cases; however, none of them induced abnormal CPK elevation, which suggests the safety of the concomitant use of statins. Other previous reports also suggested the safety or insignificance of the concomitant use of statins . On the contrary, a recent clinical study reported that the coadministration of statins was a significant independent risk factor for myopathy and rhabdomyolysis .…”
Section: Discussionmentioning
confidence: 90%
“…Other previous reports also suggested the safety or insignificance of the concomitant use of statins. [22][23][24][25][26] On the contrary, a recent clinical study reported that the coadministration of statins was a significant independent risk factor for myopathy and rhabdomyolysis. 27 Thus, the safety of the concomitant use of statins may be currently controversial, and frequent CPK monitoring or suspending of statins (if needed) should be conducted to protect patients from severe muscle injuries.…”
Section: Discussionmentioning
confidence: 98%
“…McConnell et al's study compared 233 patients receiving daptomycin (53 with statins and 180 without statins) and did not find a statistically significant difference in frequency of CK elevation (5.7% vs 1.1%, respectively; p = 0.08) [25]. Bland et al's study compared 220 patients receiving daptomycin (49 with statins vs 171 without statins) and did not find statistically significant differences in frequencies of myalgia (6.1% vs 2.9%, respectively; p = 0.38), CK levels of >1,000 U/ liter (10.2% vs 5.3%, respectively; p = 0.32), or therapy discontinuation due to CK elevations with concurrent myalgia (6.1% vs 3.5%, respectively; p = 0.42).…”
Section: Statins Interactions With Daptomycinmentioning
confidence: 95%
“…For daptomycin, systematic and manual searches identified four PK studies [21][22][23][24] and one [25] observational study, respectively. For rifampin, a systematic search identified three PK studies [26][27][28] assessing the impact of single dose and four PK studies [29][30][31][32] assessing the impact of multiple doses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation